Enhancing Students’ Learning Outcomes through the Guided Inquiry Learning Model in Trigonometry - Hidayah, Amanatul; Wibawa, Kadek Adi; Simons, Marius (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Learning trigonometry remains a challenge for many students due to teacher-centered instruction and limited opportunities for conceptual exploration. This issue highlights the urgency of implementing innovative learning models that actively engage students in constructing their understanding. This study aimed to improve students’ learning outcomes in trigonometry through the Guided Inquiry learning model. The research was conducted as Classroom Action Research (CAR) in two cycles, each consisting of two meetings, involving 30 Grade X vocational school students in Denpasar. Data were collected using essay tests to measure students’ competence in trigonometry and analyzed quantitatively based on cognitive test results. The findings showed a steady improvement in learning outcomes: prior to the intervention, only 46.67% of students achieved mastery with an average score of 61.33; in Cycle I, mastery increased to 66.67% with an average score of 73.90; and in Cycle II, mastery reached 80% with an average score of 81.97. These results indicate that the Guided Inquiry learning model effectively enhanced students’ understanding of trigonometric concepts and overall learning achievement. This improvement was influenced by the implementation of the Guided Inquiry learning model syntax, which encouraged students to develop a deeper understanding of trigonometry concepts. Therefore, it can be concluded that the Guided Inquiry learning model is effective in enhancing students’ learning outcomes.